Two antibiotic combinations with and without Vitamin E or fermentation product in rations for growing pigs - Koch, B.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Growing pigs fed ASP-250 from birth to market gained equally as well as those fed TNT. Feed conversion values were quite similar. Adding a fermentation product or vitamin E to rations did not produce consistently better gains or feed efficiency.
Swine Industry Day 1970 is known as Swine Day, 1970
Keywords: Swine; Vitamin E; Fermentation; Rations; Antibiotic